Anomalous spectral shift of localized surface plasmon resonance - Kosame, Saikiran; Josline, Mukkath Joseph; Lee, Jae Hyun; Ju, Heongkyu (Nanoscale Advances, 2024)
We report the first observation of spectral blue shift of plasmon resonance of synthesized silver nanoparticles (AgNPs) due to a negative optical nonlinearity of a local ambient medium, i.e., indigo carmine (IC) solution at around 420 nm wavelength. The blue shift occurred at a larger concentration of AgNPs or at a larger concentration of IC solution, being in obvious contrast to spectral red shift which was widely witnessed in plasmon spectral shift in a linear regime. Plasmon-enhanced local fields could excite the third-order optical nonlinearity for blue shift even under continuous (non-pulsed) light illumination. We also found that the plasmon-excited nonlinearity could allow for differential nonlinear response of the IC solution to be even greater than its differential linear response, though appearing to be somewhat inconsistent with what was generally known in light-matter interaction. The demonstrated properties of such anomalous shift of plasmon spectral peaks and its accompanying properties indicated that plasmon technologies could be exploited not only in linear but also in nonlinear aspects for critical optimization in plasmon-energy harvesting systems such as in surface enhanced spectroscopy/microscopy, biomedical imaging/sensing, laser frequency conversion, ultrashort pulse generation, and all-optical switching.
Keywords: Ambient media; Blue shift; Indigo Carmine; Localized surface plasmon resonance; Optical nonlinearity; Plasmon resonances; Property; Spectral redshifts; Spectral shift; Synthesised